Remodeling the Bone Marrow Microenvironment – A Proposal for Targeting Pro-inflammatory Contributors in MPN - Jutzi, Jonas Samuel; Mullally, Ann (Frontiers in Immunology, 2020)
Philadelphia-negative myeloproliferative neoplasms (MPN) are malignant bone marrow (BM) disorders, typically arising from a single somatically mutated hematopoietic stem cell. The most commonly mutated genes, JAK2, CALR, and MPL lead to constitutively active JAK-STAT signaling. Common clinical features include myeloproliferation, splenomegaly and constitutional symptoms. This review covers the contributions of cellular components of MPN pathology (e.g., monocytes, megakaryocytes, and mesenchymal stromal cells) as well as cytokines and soluble mediators to the development of myelofibrosis (MF) and highlights recent therapeutic advances. These findings outline the importance of malignant and non-malignant BM constituents to the pathogenesis and treatment of MF.